The Portraits of Michael the Brave Discovered by Nicolae Bălcescu in Paris - LOZA, Andrei (Studia Universitatis Babeș-Bolyai Historia, 2025)
Paris, 2 August 1847. Nicolae Bălcescu and Alexandru Golescu were working in the reading rooms of the National Library of France. They discovered a set of images that would significantly shape how later generations viewed the ruler Michael the Brave. Within a collection of prints, they identified six engraved portraits depicting the Wallachian Prince. Not all of these images entered the Romanian cultural circulation. The portraits were subjected to a process of selection and visual legitimation that would later be canonised in the 19th-century national imaginary. The present study builds on the discovery made in the summer of 1847 and traces the paths through which the identified engravings were integrated into Romanian culture. The analysis addressed both the mechanisms of dissemination and reception of these images and the ways in which they influenced the iconographic repertoire of Romanian painting in the second half of the 19th century. Moreover, the study of the engravings provides an opportunity to clarify the data concerning when and where they first appeared, as well as to interpret the inscriptions and the physiognomic features of the depicted figure. Rezumat: Paris, 2 august 1847. Nicolae Bălcescu și Alexandru Golescu se află în sălile Bibliotecii Naționale din Franța. Cei doi descoperă un set de imagini care vor influența semnificativ viziunea posterității asupra domnitorului Mihai Viteazul. Într-o colecție de stampe au identificat șase portrete de tip gravură care îl înfățișau pe domnitorul muntean. Nu toate s-au propagat în circuitul cultural românesc. Portretele au fost supuse unui proces de selecție și consacrare vizuală care avea să fie ulterior canonizată în imaginarul național din secolul al XIX-lea. Cercetarea își are punctul de plecare în descoperirea din vara anului 1847 și urmărește traseul prin care gravurile identificate au fost integrate în cultura română. Analiza vizează atât mecanismele de difuzare și receptare ale acestor imagini, cât și modul în care ele au influențat repertoriul iconografic al picturii românești din a doua jumătate a secolului al XIX-lea. În același timp, studiul gravurilor oferă prilejul de a preciza date legate de momentul și locul apariției lor, precum și de a interpreta inscripțiile și caracteristicile fizionomice ale personajului reprezentat. Cuvinte-cheie: Mihai Viteazul; gravură; iconografie; Nicolae Bălcescu; secolul al XIX-lea; pictură istorică; canon visual, Aegidius Sadeler, Dominicus Custos.